Modified aluminum nitride and preparation method thereof
By depositing dopamine on the surface of aluminum nitride and forming a polydopamine coating, the problem of easy hydrolysis of aluminum nitride is solved, and its hydrolysis resistance and biocompatibility are significantly improved.
Patent Information
- Application Number
- CN202510045446.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Due to its extremely easy hydrolysis performance, aluminum nitride limits its application in high-demand environments such as 5G base stations and automotive sensing systems.
By mixing aluminum nitride powder with dispersant and alcohol solvent for grinding, nanoscale aluminum nitride powder is obtained, and dopamine is deposited on the surface of aluminum nitride through a freeze-drying process, which self-polymerizes to form polydopamine coated on nitride. Aluminum surface.
The hydrolysis resistance of aluminum nitride is improved, and its stability and biocompatibility in high humidity environments are improved.
Smart Images

Figure CN119461269A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aluminum nitride modification, and in particular to modified aluminum nitride and a preparation method thereof. Background Art
[0002] Aluminum nitride (AlN) is a wide bandgap semiconductor with many advantages, such as excellent thermodynamic properties. Its actual thermal conductivity is 100 W·m -1 ·K -1 Up to 260W·m -1 ·K -1 It is considered to be a new generation of heat dissipation material to replace alumina; it has good insulation properties and can be used as a good insulation material; its mechanical properties are higher than those of Si3N4 and Al2O3 (for example, the excess ratio is 50%); it has excellent high temperature and high corrosion resistance.
[0003] However, aluminum nitride is highly hygroscopic, and existing data show that aluminum nitride powder placed in ethanol is almost completely hydrolyzed after 15 days. The extremely easy hydrolysis of aluminum nitride limits its application in 5G base stations, automotive sensor systems, etc. Summary of the invention
[0004] The invention provides a modified aluminum nitride and a preparation method thereof, which can improve the hydrolysis resistance of the aluminum nitride.
[0005] The invention provides a preparation method of modified aluminum nitride, comprising: grinding a mixture comprising aluminum nitride powder, a dispersant and an alcohol solvent to obtain a nano-scale aluminum nitride powder with a particle size of 50-400 nm; subjecting the nano-scale aluminum nitride powder to a first freeze-drying treatment to obtain a freeze-dried aluminum nitride powder; mixing a solution comprising dopamine and the freeze-dried aluminum nitride powder, and then subjecting the mixture to a second freeze-drying treatment to obtain the modified aluminum nitride.
[0006] Optionally, the dispersant includes one or more of polyacrylate, sodium dodecylbenzene sulfonate, hexadecyltrimethylammonium bromide, polymethylbenzene salt, sodium tripolyphosphate, sodium hexametaphosphate and sodium pyrophosphate; and / or, the alcohol solvent includes one or more of ethanol and butanol; and / or, during the grinding process, the abrasive used includes aluminum oxide; and / or, the grinding linear speed is 8 m / s~13 m / s.
[0007] Optionally, the first freeze-drying treatment includes a first stage and a second stage, wherein the temperature of the first stage is -20°C~-30°C, and the vacuum degree is 10~100Pa, and the temperature of the second stage is -25°C~40°C, and the vacuum degree is 20~50Pa.
[0008] Optionally, the solution comprising dopamine further comprises a solvent, and the solvent comprises one or more of methanol, ethanol, dimethylformamide, and dimethyl sulfoxide.
[0009] Optionally, the dopamine comprises dopamine hydrochloride.
[0010] Optionally, in the solution comprising dopamine, the concentration of dopamine is 0.1 mol / L to 0.5 mol / L.
[0011] Optionally, the second freeze-drying treatment includes a third stage and a fourth stage, wherein the temperature of the third stage is -10°C~10°C, and the vacuum degree is 20~50Pa, and the temperature of the fourth stage is 25°C~40°C, and the vacuum degree is 10~50Pa.
[0012] Optionally, the process of mixing the solution including dopamine and the freeze-dried aluminum nitride powder and then performing a second freeze-drying treatment to obtain the modified aluminum nitride includes: dripping the solution including dopamine into the freeze-dried aluminum nitride powder, then ultrasonically treating it, and then performing a second freeze-drying treatment to obtain the modified aluminum nitride.
[0013] Optionally, the ultrasonic treatment time is 10 to 30 minutes.
[0014] The present invention provides a modified aluminum nitride, and the modified aluminum nitride is obtained according to the preparation method as described above.
[0015] The present invention provides a modified aluminum nitride and a preparation method thereof. Based on a freeze-drying process, dopamine is deposited on the surface of aluminum nitride, so that dopamine forms polydopamine through self-polymerization and is coated on the surface of the aluminum nitride inorganic material. The polydopamine-coated aluminum nitride structure can be used as a surface functionalized coating of the modified aluminum nitride to form a polydopamine-coated aluminum nitride structure, which can not only inhibit the hydrolysis of the inner aluminum nitride, but also improve its hydrolysis resistance and enhance the biocompatibility of the modified aluminum nitride inorganic material. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0017] Figure 1 A schematic flow chart of a method for preparing modified aluminum nitride provided in an embodiment of the present invention;
[0018] Figure 2The X-ray diffraction patterns of the modified aluminum nitride (dopamine-coated aluminum nitride powder) of Example 1, Example 3 and Comparative Example 1 and the unmodified aluminum nitride powder ( Figure 2 a in the figure is the part within the red frame in b). DETAILED DESCRIPTION
[0019] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below. The specific implementation methods listed below are only for describing the principles and features of the present invention. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0020] Freeze drying utilizes the sublimation phenomenon of ice crystals to directly sublimate the water in the material into water vapor in a highly vacuum environment, thereby achieving the purpose of drying the material. Since the water in the material does not go through the process of ice crystal melting during the freeze drying process, the freeze drying process has the advantages of small loss of volatile components, maintaining the original properties and structure of the material, no concentration problems, and no side reactions under vacuum, making freeze drying widely used in scientific research. Dopamine, as a surfactant, is often used for surface modification of materials. The reaction conditions of its self-polymerization reaction are mild, and the polydopamine produced by self-polymerization is rich in functional groups such as amino groups, which can provide more possibilities for further functionalization of the material after surface modification.
[0021] Based on this, the embodiment of the present invention provides a method for preparing modified aluminum nitride, such as Figure 1 As shown, the method comprises: grinding a mixture of aluminum nitride (AlN) powder, a dispersant and an alcohol solvent to obtain a nano-scale aluminum nitride powder with a particle size of 50 to 400 nm; subjecting the nano-scale aluminum nitride powder to a first freeze-drying treatment to obtain a freeze-dried aluminum nitride powder; mixing a solution comprising dopamine and the freeze-dried aluminum nitride powder, and then subjecting the mixture to a second freeze-drying treatment to obtain a modified aluminum nitride (chemically coated hydrolysis-resistant AlN powder).
[0022] In the above-mentioned preparation method system of modified aluminum nitride, dopamine is deposited on the surface of aluminum nitride based on a freeze-drying process, so that dopamine forms polydopamine through self-polymerization and is coated on the surface of the aluminum nitride inorganic material. It can be used as a surface functional coating of the modified aluminum nitride to form a polydopamine-coated aluminum nitride structure, which can not only inhibit the hydrolysis of the inner layer of aluminum nitride, but also improve its hydrolysis resistance and enhance the biocompatibility of the modified aluminum nitride inorganic material.
[0023] In addition, dopamine self-polymerizes on the surface of modified aluminum nitride to generate polydopamine. The surface of polydopamine is rich in functional groups such as amino groups, which can provide action sites for further modification (functionalization) of modified aluminum nitride, help improve its reprocessing performance, and provide a new idea for solving the problem of poor reprocessability of alumina as a covalent compound of hexagonal wurtzite. It has great application potential in actual industrial production.
[0024] The above preparation method has mild reaction conditions, simple operation process and does not require harsh conditions such as high temperature or oxygen-free.
[0025] Figure 2 The X-ray diffraction patterns of the modified aluminum nitride (dopamine-coated aluminum nitride powder) of Example 1, Example 3 and Comparative Example 1 and the unmodified aluminum nitride powder ( Figure 2 a is the part in the red box in b), from Figure 2 It can be seen that the unmodified aluminum nitride powder has only three obvious characteristic diffraction peaks, while the modified aluminum nitride of Examples 1 and 3 both have characteristic diffraction peaks of polydopamine at around 28°. In Comparative Example 1, polyacrylic acid is used instead of dopamine hydrochloride, and the aluminum nitride thereof will not have this diffraction peak.
[0026] The embodiment of the present invention does not particularly limit the particle size of the aluminum nitride powder, which may be, for example, about 10 microns.
[0027] The mixture including aluminum nitride powder, dispersant and alcohol solvent is ground to obtain nano-scale aluminum nitride powder with a particle size of 50 to 400 nm. In some embodiments, the particle size of the nano-scale aluminum nitride powder is normally distributed (more obvious normal distribution), which is conducive to the smooth progress of the subsequent preparation process and to improving the hydrolysis resistance and reprocessing performance of the modified aluminum nitride.
[0028] It can be understood that the above grinding process is to grind the aluminum nitride powder under the action of the alcohol solvent and the dispersant to form a nano-scale aluminum nitride powder (aluminum nitride slurry) with a uniform particle size of 50-400 nm.
[0029] In a specific implementation, a sand mill can be used to grind the mixture including aluminum nitride powder, dispersant and alcohol solvent. The linear speed of the sand mill can be 8m / s to 13m / s, such as 10, 11, 12, 13, 15, 16, 20, 30, 40, 50, 60m / s or any two thereof.
[0030] Furthermore, in the above-mentioned grinding process, the abrasive (the ball stone used) used may include aluminum oxide.
[0031] The above-mentioned dispersant may include one or more of polyacrylate, sodium dodecylbenzene sulfonate, hexadecyltrimethylammonium bromide, polymethylbenzene acid salt, sodium tripolyphosphate, sodium hexametaphosphate and sodium pyrophosphate.
[0032] The alcohol solvent may include one or more of ethanol (eg, anhydrous ethanol) and butanol.
[0033] The nano-scale aluminum nitride powder (aluminum nitride slurry) is subjected to a first freeze-drying treatment to obtain freeze-dried aluminum nitride powder. The freeze-drying technology can make the nano-scale aluminum nitride powder (aluminum nitride slurry) form ultra-dispersed loose nano-aluminum nitride particles, which is beneficial to improving the effect of dopamine deposition and forming a dopamine-coated aluminum nitride structure, which is beneficial to improving the hydrolysis resistance and reprocessability of the modified aluminum nitride.
[0034] In some embodiments, the first freeze-drying process includes a first stage and a second stage, wherein the temperature of the first stage is -20°C~-30°C, the vacuum degree is 10~100 Pa, and the temperature of the second stage is -25°C~40°C, and the vacuum degree is 20~50 Pa. First, in the first stage, by controlling the conditions to a temperature of -20°C~-30°C and a vacuum degree of 10~100 Pa, the slurry can be frozen, and then enter the second stage (second stage freeze drying), -25°C~40°C, and the vacuum degree is 20~50Pa, which can remove the residual liquid water in the frozen slurry, and then obtain the freeze-dried aluminum nitride powder (ultra-dispersed loose nano aluminum nitride particles after freeze drying), which is beneficial to improve the hydrolysis resistance and reprocessing properties of the modified aluminum nitride.
[0035] The solution including dopamine and the aluminum nitride powder after freeze drying are mixed, and then a second freeze drying treatment is performed to obtain modified aluminum nitride. Based on the freeze drying technology, the dopamine-aluminum nitride suspension is subjected to a second freeze drying treatment, dopamine can be deposited on the surface of aluminum nitride, and dopamine is self-polymerized into polydopamine coated on the surface of aluminum nitride to form a polydopamine-coated aluminum nitride structure, which can improve its hydrolysis resistance and provide active sites for subsequent further functionalization to improve its reprocessability.
[0036] It is understandable that the above-mentioned solution including dopamine also includes a solvent.
[0037] Specifically, the solvent may include one or more of methanol, ethanol, dimethylformamide (DMF), and dimethyl sulfoxide (DMSO), and the dopamine may include dopamine hydrochloride (hydrochloride).
[0038] In the solution including dopamine, the concentration of dopamine can be 0.1 mol / L to 0.5 mol / L, for example, 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L or a range consisting of any two thereof.
[0039] In specific implementation, dopamine and a solvent may be mixed to prepare (configure) the above-mentioned solution including dopamine (alcoholic dopamine solution). It should be noted that before using a volumetric flask, attention should be paid to leak detection, and the solution should be left to stand until it returns to room temperature before pipetting.
[0040] In some embodiments, the second freeze-drying process includes a third stage and a fourth stage, wherein the temperature of the third stage is -10°C~10°C, and the vacuum degree is 20~50Pa, and the temperature of the fourth stage is 25°C~40°C, and the vacuum degree is 10~50Pa.
[0041] It is understandable that before the second freeze-drying, the material can be pre-frozen to a temperature below the sub-zero eutectic point, and then the third stage of freeze-drying (freeze-drying before the ice crystals disappear) is performed to freeze the mixture (suspension) of dopamine and aluminum nitride, and then the fourth stage of freeze-drying is performed to remove residual liquid water, thereby obtaining modified aluminum nitride.
[0042] In addition, the process of mixing the solution including dopamine and the freeze-dried aluminum nitride powder and then performing a second freeze-drying treatment to obtain the modified aluminum nitride may include: adding the solution including dopamine to the freeze-dried aluminum nitride powder (dried nano aluminum nitride) (for example, dripping under the dispersion effect of a cell crusher), then ultrasonically treating to obtain a dopamine aluminum nitride suspension, and then performing a second freeze-drying treatment to obtain the modified aluminum nitride. The above operation helps dopamine to be better coated on the surface of aluminum nitride, further improving the hydrolysis resistance and reprocessability of the modified aluminum nitride.
[0043] Furthermore, the ultrasonic treatment time can be 10 to 30 minutes.
[0044] The embodiment of the present invention further provides a modified aluminum nitride, which can be obtained according to the above-mentioned preparation method. The modified aluminum nitride (chemically coated hydrolysis-resistant AlN powder) has good hydrolysis resistance and reprocessability.
[0045] It is understandable that the first freeze-drying treatment and the second freeze-drying treatment are both carried out in a freeze-drying device. The ambient temperature of the device can be maintained at 10°C to 30°C, and the relative humidity is less than 80%. In addition, before the first freeze-drying treatment, the nano-scale aluminum nitride powder (aluminum nitride slurry) or the mixture of the solution including dopamine and the aluminum nitride powder after freeze-drying can be placed in a container (such as a beaker), sealed with a plastic wrap, and some small holes are pierced in the sealed plastic wrap with a tool such as tweezers to facilitate the sublimation of residual water.
[0046] The present invention is further described below by specific examples and comparative examples. Unless otherwise specified, the reagents, materials and instruments used below are all conventional reagents, conventional materials and conventional instruments, which can be commercially available, and the reagents and materials involved can also be synthesized by conventional synthesis methods.
[0047] The sources of some of the raw materials used in the following examples and comparative examples are as follows:
[0048] Aluminum nitride powder with a particle size of 10 μm: A-2 powder from Ningxia Aisenda Technology Co., Ltd.;
[0049] Sodium dodecylbenzene sulfonate: Shanghai Jizhi Biochemical Technology Co., Ltd. (brand Acmec), ABS10-14; purity AR;
[0050] Sodium hexametaphosphate: Shanghai McLean Biochemical Technology Co., Ltd. (brand McLean), purity 65%;
[0051] Sodium tripolyphosphate: Alfa Aesar (China) Chemical Co., Ltd. (brand Alfa Aesar), purity AR;
[0052] Sodium pyrophosphate: Shanghai McLean Biochemical Technology Co., Ltd. (brand McLean), purity 99%;
[0053] Polyacrylic acid: Beijing Merida Technology Co., Ltd., brand MREDA, average viscosity average molecular weight (average Mv) is ~ 450000, purity AR;
[0054] Dopamine hydrochloride: Shanghai Aladdin Biochemical Technology Co., Ltd. (brand Aladdin), purity BR, storage temperature is -20℃;
[0055] Anhydrous ethanol: Shanghai McLean Biochemical Technology Co., Ltd. (brand McLean), purity 99.5%;
[0056] Methanol: Shanghai McLean Biochemical Technology Co., Ltd. (brand McLean), purity 99.8%, water content ≤50ppm;
[0057] Butanol: Anhui Zesheng Technology Co., Ltd. (brand Anage), purity ≥99.5%.
[0058] Example 1
[0059] This embodiment provides a method for preparing modified aluminum nitride, comprising:
[0060] 1) grinding a mixture of aluminum nitride powder with a particle size of 10 μm, polyacrylate and anhydrous ethanol to obtain nano-scale aluminum nitride powder (aluminum nitride slurry) with a particle size of 300 nm; wherein the grinding linear speed is 11 m / s, and aluminum oxide balls are used as abrasives;
[0061] 2) subjecting the nano-scale aluminum nitride powder to a first freeze-drying treatment, wherein the first freeze-drying treatment includes a first stage and a second stage, wherein the temperature of the first stage is -30°C and the vacuum degree is 15Pa, so that the slurry is frozen, and the temperature of the second stage is -25°C and the vacuum degree is 30Pa, so that residual liquid water is removed to obtain freeze-dried aluminum nitride powder (ultra-dispersed loose nano-aluminum nitride particles after freeze-drying);
[0062] 3) Using dopamine hydrochloride as the solute and methanol as the solvent, a dopamine solution (alcoholic dopamine solution) having a dopamine concentration of 0.1 mol / L is prepared;
[0063] 4) Under the dispersing action of a cell crusher, the alcohol dopamine solution is dripped into the freeze-dried aluminum nitride powder, and then ultrasonically treated for 30 minutes to obtain a dopamine aluminum nitride suspension, and then a second freeze-drying treatment is performed, wherein the second freeze-drying treatment includes a third stage and a fourth stage, wherein the temperature of the third stage is -10°C and the vacuum degree is 20Pa to freeze the suspension, and the temperature of the fourth stage is 28°C and the vacuum degree is 15Pa to remove residual liquid water to obtain modified aluminum nitride (dopamine-coated aluminum nitride nanopowder).
[0064] The above-mentioned nano-scale aluminum nitride powder (aluminum nitride slurry) with a particle size of 300 nm was diluted and dispersed in anhydrous ethanol, and its particle size distribution was measured. It showed a relatively obvious normal distribution, indicating that its particle size distribution was narrow, which is beneficial to the subsequent modification process.
[0065] Example 2
[0066] This embodiment is basically the same as Embodiment 1, except that:
[0067] In step 1), anhydrous ethanol is replaced by butanol, polyacrylate is replaced by sodium dodecylbenzene sulfonate, and the grinding linear speed is adjusted to 13 m / s to obtain a nano-scale aluminum nitride powder (aluminum nitride slurry) with a particle size of 200 nm; the above-mentioned nano-scale aluminum nitride powder (aluminum nitride slurry) with a particle size of 200 nm is diluted and dispersed in anhydrous ethanol, and its particle size distribution is measured, which shows a relatively obvious normal distribution, indicating that its particle size distribution is narrow, which is beneficial to the subsequent modification process;
[0068] In step 2), the temperature of the first stage is -30°C;
[0069] In step 3), the concentration of dopamine in the solution including dopamine (alcoholic dopamine solution) is 0.2 mol / L;
[0070] Other conditions remain unchanged.
[0071] Example 3
[0072] This embodiment is basically the same as Embodiment 1, except that:
[0073] In step 1), polyacrylate is replaced by sodium hexametaphosphate, and the grinding linear speed is adjusted to 15 m / s to obtain nano-scale aluminum nitride powder (aluminum nitride slurry) with a particle size of 100 nm;
[0074] In step 2), the temperature of the first stage is -20°C;
[0075] In step 3), the concentration of dopamine in the solution including dopamine (alcoholic dopamine solution) is 0.4 mol / L;
[0076] Other conditions remain unchanged.
[0077] Example 4
[0078] This embodiment is basically the same as Embodiment 1, except that:
[0079] In step 1), polyacrylate is replaced by polymethyl methacrylate and sodium tripolyphosphate in a mass ratio of 1:1, anhydrous ethanol is replaced by butanol, and the grinding line speed is 13 m / s to obtain nano-scale aluminum nitride powder (aluminum nitride slurry) with a particle size of 50 nm; other conditions remain unchanged.
[0080] Example 5
[0081] This embodiment is basically the same as Embodiment 1, except that:
[0082] In step 1), polyacrylate is replaced with sodium hexametaphosphate and sodium pyrophosphate in a mass ratio of 1:1 to obtain a nano-scale aluminum nitride powder (aluminum nitride slurry) with a particle size of 400 nm;
[0083] In step 3), the concentration of dopamine in the dopamine solution (alcoholic dopamine solution) is 0.6 mol / L; other conditions remain unchanged.
[0084] Comparative Example 1
[0085] This comparative example is basically the same as Example 1, except that:
[0086] Dopamine hydrochloride was replaced by polyacrylic acid, and other conditions remained unchanged.
[0087] Comparative Example 2
[0088] This comparative example is basically the same as Example 1, except that:
[0089] Step 4) comprises: under the dispersing action of a cell crusher, dripping the alcohol dopamine solution into the freeze-dried aluminum nitride powder, then ultrasonically treating for 30 minutes to obtain a dopamine aluminum nitride suspension, and then drying in an oven, wherein the drying temperature is 60° C., removing residual liquid water, and obtaining modified aluminum nitride (dopamine-coated aluminum nitride nanopowder); other conditions remain unchanged.
[0090] Test example
[0091] The hydrolysis resistance of the modified aluminum nitride (chemically coated hydrolysis-resistant AlN powder) of each embodiment and comparative example was tested:
[0092] Anti-hydrolysis performance: AlN powder is mixed with water to form a suspension. In the suspension, AlN powder reacts with water to generate amorphous AlOOH and ammonia. AlOOH dissolves and recrystallizes to form Al(OH)3, which coats the surface of the AlN powder. Ammonia dissolves in water to generate ammonia ions and hydroxide ions. Hydroxyl ions will cause the pH of the suspension of AlN powder and water to increase, that is, the pH of the suspension of AlN powder and water will remain stable first, and then increase with the hydrolysis of AlN powder; the pH of the suspension after AlN powder with poor anti-hydrolysis performance is mixed with water will increase in a short time, that is, the stable time is short, while the pH of the suspension after AlN powder with good anti-hydrolysis performance is mixed with water will not increase in a short time, that is, the stable time is long. Based on this, the embodiment of the present invention determines whether the AlN powder is hydrolyzed by testing the time that the pH value of the suspension after the modified aluminum nitride of each embodiment and comparative example is mixed with water to remain stable. Specifically, the longer the pH remains stable, the better the hydrolysis resistance of the AlN powder. The test process includes: mixing the modified aluminum nitride of each embodiment and comparative example with water to prepare a 5 wt% suspension, and then using Shanghai Lei's pHS-3E pH meter at room temperature to measure the pH change of the above suspension for at least 48 hours, and recording the time when the pH remains stable (the absolute value of the pH change is less than 1).
[0093] Test results
[0094] Table 1
[0095]
[0096] At the beginning of the test, the pH of the unchemically coated AlN powder quickly (within 10 minutes) rose to about 11, generating aluminum hydroxide. When this hydrolysis product exists in the powder, it will significantly reduce the thermal conductivity and mechanical properties of the powder and the subsequent ceramic substrate. The pH of the chemically coated hydrolysis-resistant AlN powder can remain stable for more than 24 hours at room temperature. In addition, in Example 5, due to the large particle size of the obtained aluminum nitride powder, occasional incomplete coating may occur, and the anti-hydrolysis time is 16 hours. However, the pH of the oven-dried AlN powder can only remain stable for 5 hours due to problems such as incomplete coating or poor uniformity.
[0097] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing modified aluminum nitride, characterized in that: include: Grinding a mixture of aluminum nitride powder, a dispersant, and an alcohol solvent to obtain nano-scale aluminum nitride powder with a particle size of 50 to 400 nm; The nano-sized aluminum nitride powder is subjected to a first freeze-drying treatment to obtain freeze-dried aluminum nitride powder; The solution including dopamine and the freeze-dried aluminum nitride powder are mixed, and then subjected to a second freeze-drying treatment to obtain the modified aluminum nitride.
2. The method for preparing modified aluminum nitride according to claim 1, characterized in that: The dispersant includes one or more of polyacrylate, sodium dodecylbenzene sulfonate, hexadecyltrimethylammonium bromide, polymethylbenzene acid salt, sodium tripolyphosphate, sodium hexametaphosphate and sodium pyrophosphate; And / or, the alcohol solvent includes one or more of ethanol and butanol; And / or, during the grinding process, the abrasive used includes aluminum oxide; And / or, the grinding linear speed is 8 m / s to 13 m / s.
3. The method for preparing modified aluminum nitride according to claim 1 or 2, characterized in that: The first freeze-drying process includes a first stage and a second stage, wherein the temperature of the first stage is -20°C to -30°C, and the vacuum degree is 10 to 100 Pa, and the temperature of the second stage is -25°C to 40°C, and the vacuum degree is 20 to 50 Pa.
4. The method for preparing modified aluminum nitride according to claim 1 or 2, characterized in that: The solution comprising dopamine further comprises a solvent, and the solvent comprises one or more of methanol, ethanol, dimethylformamide, and dimethyl sulfoxide.
5. The method for preparing modified aluminum nitride according to claim 1 or 2, characterized in that: The dopamine includes dopamine hydrochloride.
6. The method for preparing modified aluminum nitride according to claim 1 or 2, characterized in that: In the solution comprising dopamine, the concentration of dopamine is 0.1 mol / L to 0.5 mol / L.
7. The method for preparing modified aluminum nitride according to claim 1 or 2, characterized in that: The second freeze-drying process includes a third stage and a fourth stage, wherein the temperature of the third stage is -10°C~10°C, and the vacuum degree is 20~50Pa, and the temperature of the fourth stage is 25°C~40°C, and the vacuum degree is 10~50Pa.
8. The method for preparing modified aluminum nitride according to claim 1 or 2, characterized in that: The process of mixing the solution including dopamine and the freeze-dried aluminum nitride powder and then performing a second freeze-drying treatment to obtain the modified aluminum nitride includes: dripping the solution including dopamine into the freeze-dried aluminum nitride powder, then ultrasonically treating it, and then performing a second freeze-drying treatment to obtain the modified aluminum nitride.
9. The method for preparing modified aluminum nitride according to claim 8, characterized in that: The ultrasonic treatment time is 10 to 30 minutes.
10. A modified aluminum nitride, characterized in that: The modified aluminum nitride is obtained according to the preparation method of the modified aluminum nitride according to any one of claims 1 to 9.
Citation Information
Patent Citations
Hydrolysis resistant aluminum nitride powder, and preparation method and application thereof
CN105565823A
Method for synthesizing aluminum nitride power
CN105837223A
Silicone rubber thermal interface material with high tear resistance and high thermal conductivity for LED and preparation method
CN106280467A
Dopamine coated nano silicon dioxide modified conductive and heat-conducting glass fiber composite material and preparation method thereof
CN107189495A
High-heat-dissipation television plastic shell ABS (acrylonitrile butadiene-styrene) alloy material
CN109486092A
Cited By
Cool washing-resistant bio-based nylon 56 fabric and preparation method thereof
CN120211109A
High-strength aluminum nitride ceramic substrate and preparation method thereof
CN120329051A
High-strength aluminum nitride ceramic substrate and method for manufacturing the same
CN120329051B
Graphene-coated aluminum nitride high-thermal-conductivity powder and preparation method thereof
CN122080499A